Health Benefits of Endurance Training: Implications of the Brain-Derived Neurotrophic Factor—A Systematic Review - Włodzimierz Mrówczyński (Neural Plasticity)
This article presents a concept that wide expression of brain-derived neurotrophic factor (BDNF) and its receptors (TrkB) in the nervous tissue, evoked by regular endurance training (ET), can cause numerous motor and metabolic adaptations, which are beneficial for human health. The relationships between the training-evoked increase of endogenous BDNF and molecular and/or physiological adaptations in the nervous structures controlling both motor performance and homeostasis of the whole organism have been presented. Due to a very wide range of plastic changes that ET has exerted on various systems of the body, the improvement of motor skills and counteraction of the development of civilization diseases resulting from the posttraining increase of BDNF/TrkB levels have been discussed, as important for people, who undertake ET. Thus, this report presents the influence of endurance exercises on the (1) transformation of motoneuron properties, which are a final element of the motor pathways, (2) reduction of motor deficits evoked by Parkinson disease, and (3) prevention of the metabolic syndrome (MetS). This review suggests that the increase of posttraining levels of BDNF and its TrkB receptors causes simultaneous changes in the activity of the spinal cord, the substantia nigra, and the hypothalamic nuclei neurons, which are responsible for the alteration of the functional properties of motoneurons innervating the skeletal muscles, for the enhancement of dopamine release in the brain, and for the modulation of hormone levels involved in regulating the metabolic processes, responsively. Finally, training-evoked increase of the BDNF/TrkB leads to a change in a manner of regulation of skeletal muscles, causes a reduction of motor deficits observed in the Parkinson disease, and lowers weight, glucose level, and blood pressure, which accompany the MetS. Therefore, BDNF seems to be the molecular factor of pleiotropic activity, important in the modulation processes, underlying adaptations, which result from ET.